Pregnancy rates of dairy cows at first service:influence of gonadotropin-releasing hormoneand timing of AI relative to estrus - Jeffrey S. Stevenson; M.O. Mee; R.K. Scoby; Y. Folman (Kansas Agricultural Experiment Station Research Reports, 1989)
We demonstrated that gonadotropin-releasing hormone (GnRH or Cystorelin®) failed to improve pregnancy rates at the first service. When GnRH injection and insemination are both carried out either in early or late estrus or if cows are bred in early estrus and given a GnRH injection later in estrus, pregnancy rates are reduced by 9 to 13 percentage points compared to breeding according to the am-pm rule without GnRH treatment (control). Pregnancy rates of cows injected with GnRH early in estrus and bred in late estrus were similar to controls injected with saline and inseminated late in estrus (46 vs 43%). Altering the time of breeding and the time of GnRH injection to either early or late estrus did not improve pregnancy rates. We continue to recommend using GnRH only for repeat breeders, because GnRH consistently improves pregnancy rates at 3rd or 4th service, but not at first services.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Pregnancy rates; Gonadotropin-releasing hormone (GnRH or Cystorelin®); AI; Estrus